Gambaran Penggunaan Antıhıpertensı pada Pasıen ST- Elevatıon Myocardıal Infractıon - Khofifah aulia; Irma Novrianti; Jufri Ubrusun (Journal Borneo, 2022)
ST-Elevation Myocardial Infraction (STEMI) is caused by several factors, mainly due to cardiovascular disorders. There are several complaints from STEMI, such as chest pain, elevated enzymes, and ST elevation on electrocardiogram examination. One of the major factors in the occurrence of STEMI is hypertension. The more severe the hypertension condition will slowly damage the blood vessel walls causing swelling, which leads to STEMI. This study aimed to see the use of antihypertensives in stemmy patients who were using fibrinolytic therapy. This research method is descriptive retrospective by looking at the medical records of STEMI patients who received antihypertensive treatment at the Emergency Room (ER) and were hospitalized at Tarakan City "X" Hospital for the 2017-2018 period. Based on the research, it was found that 55 patients used antihypertensives. The highest classification of blood pressure when admitted to the hospital was in stage II conditions based on JNC VII in 15 people (27.28%), and the classification of blood pressure when leaving the hospital was found to be in normal condition in 23 people (41.82%). The most antihypertensive used in "X" Hospital in Tarakan city is the ACE-Inhibitor group, namely captopril, with a percentage of 10.90% in the ER, and the Beta blocker group, namely bisoprolol fumarate with a percentage of 65.46% in the Inpatient Room.